Pengoperasian Rescue Boat Saat Drill Keselamatan di SPOB (Self Propelled Oil Barge) Julvinda - Wanda Afrizal; Muhammad Sapril Siregar; Sabaruddin Sabaruddin (Departement of Mathematics Education, 2023)
Rescue boat training is a form of knowledge about saving oneself and others in the event of an emergency at sea. The purpose of this study was to determine the cause of delays when lowering the rescue boat, and to determine the knowledge of the crew about procedures during an emergency. The method used is the observation method, namely direct observation of the object under study. Through observation and research with data collection techniques and get closer to the existing problems, because with the observation method the compiler can directly hold activities in the field. Observations that the author made by making direct observations when the authors carried out marine practice. In addition, observation is a very important data collection tool in descriptive research. The results of research and discussion of problems regarding delays in lowering Rescue boat during an emergency, The rescue boat should have been able to descend within 3-5 minutes, but due to the lack of understanding and skills of the ship's crew, making the rescue boat descend took up to 7-8 minutes and based on observations in the field when carrying out rescue boat lowering drills on the SPOB. Julvinda ship, the author can conclude how to lower rescue boat using gravity goddesses there are 66% of respondents who can mastering the procedure well in lowering rescue boat can be categorized as skilled and 33% of respondents who do not understand the procedures for lowering rescue boat with machines or remotely in lowering rescue boat during emergency drills. Key Words: Rescue Boat; Maritime; Education.